A comprehensive assessment of self-reported symptoms among patients harboring an unruptured intracranial aneurysm - Hackett, Ashia M.; Koester, Stefan W.; Rhodenhiser, Emmajane G.; Scherschinski, Lea; Rulney, Jarrod D.; Naik, Anant; Nico, Elsa; Eberle, Adam T.; Hartke, Joelle N.; Fox, Brandon M.; Winkler, Ethan A.; Catapano, Joshua S.; et al. (Frontiers in Surgery, 2023)
Background Approximately 3.2%–6% of the general population harbor an unruptured intracranial aneurysm (UIA). Ruptured aneurysms represent a significant healthcare burden, and preventing rupture relies on early detection and treatment. Most patients with UIAs are asymptomatic, and many of the symptoms associated with UIAs are nonspecific, which makes diagnosis challenging. This study explored symptoms associated with UIAs, the rate of resolution of such symptoms after microsurgical treatment, and the likely pathophysiology. Methods A retrospective review of patients with UIAs who underwent microsurgical treatment from January 1, 2014, to December 31, 2020, at a single quaternary center were identified. Analyses included the prevalence of nonspecific symptoms upon clinical presentation and postoperative follow-up; comparisons of symptomatology by aneurysmal location; and comparisons of patient demographics, aneurysmal characteristics, and poor neurologic outcome at postoperative follow-up stratified by symptomatic versus asymptomatic presentation. Results The analysis included 454 patients; 350 (77%) were symptomatic. The most common presenting symptom among all 454 patients was headache (n = 211 [46%]), followed by vertigo (n = 94 [21%]), cognitive disturbance (n = 68[15%]), and visual disturbance (n = 64 [14%]). Among 328 patients assessed for postoperative symptoms, 258 (79%) experienced symptom resolution or improvement. Conclusion This cohort demonstrates that the clinical presentation of patients with UIAs can be associated with vague and nonspecific symptoms. Early detection is crucial to prevent aneurysmal subarachnoid hemorrhage. It is imperative that physicians not rule out aneurysms in the setting of nonspecific neurologic symptoms.